Transformative Consumption and Acculturation of Ukrainian Female Consumers in Sweden - Kolyaka,Tetyana (2010)
The consumption structure, and generally lifestyles in Post-Soviet countries are undergoing drastic changes over the last 20 years of liberalization. The scarcity of consumer goods over the Soviet period, followed by the wide availability of goods and freedom to choose, resulted in the consumption model in countries of Post-communistic Bloc that is significantly different from that in countries with longer history of democracy and market economy, such as Sweden. This study is built upon the stories of four women who were born and raised in Ukraine before Perestroika of 1980’s and moved to Sweden after the collapse of USSR. The author aims to observe how dreams, aspirations and everyday life of Ukrainian female consumers brought up within the planned economy with the scarcity or limited availability of basic consumer goods changed after moving to Sweden. The focus is particularly drawn upon the consumption transformation of immigrants who are fully integrated in the Scandinavian mentality milieu, and shows how the Ukrainian female immigrants in Sweden go through the acculturation phases, that were defined by Oberg (1960) in his study of the migrants’ cultural shock and adaptation to the host environment. The findings indicate that the consumer acculturation process deviations of the adult Ukrainian female immigrants in Sweden are considerable, and that they are stably dependent of the effect of education and culture capital gained before the immigration, occupational class position in Sweden compared to the status before moving, and the extent of the contact with dominant culture.
Keywords: Consumer Transition; Acculturation Phases; Cultural Globalization; Post-Soviet Female Immigration; Management of enterprises; Företagsledning, management